Contrast Bath Treatment in Post Stroke CRPS: Contrast Bath Treatment for Post Stroke CRPS - Raza, Ali; Afzal , Binash; Hanif , Muhammad (Pakistan Journal of Health Sciences, 2022)
Complex Regional Pain Syndrome (CRPS) is a painful and incapacitating disorder that typically develops as a result of injury or surgery and is linked to severe discomfort and disability. It is one of the common complications in stroke patients. A therapeutic technique known as a contrast bath includes alternate bathing in both warm and cold water. This method might aid in enhancing blood flow within your body. Case Summary: We present a case of complicated regional pain syndrome, a stroke-related complication in a 55-year-old businessman treated with a contrast bath. Conclusion: Contrast bath treatment improves pain in patient’s right arm, ranges of upper extremities and this technique also improves blood circulation.